Exploring the Development of Comic Media Research to Increase Elementary School Students’ Reading Interest Over the Last Decade - Rahmawati, Oka Mania; Oktaviani, Anna Maria; Gunardi, Ari (Universitas Pendidikan Ganesha, 2025)
Systematic studies mapping research trends and dynamics related to the potential of comics in learning, particularly in the context of increasing reading interest in elementary school students, are still rare. However, this potential is increasingly recognised in various studies. This study aims to analyse trends and patterns of scientific publications regarding the use of comics in increasing reading interest in elementary school students over the past decade (2015–2025). This study employed a quantitative design with bibliometric analysis methods, utilising data from 1,990 scientific articles obtained through the Dimensions.ai platform. Data were analysed using Bibliometrix R-Package software, which includes visualisation techniques such as word clouds and world maps, as well as citation and co-authorship analysis, which can be viewed through the Dimensions.ai platform. The results show a significant increase in the number of publications from 2020 to 2024, with researchers from various countries contributing to the growth. The dominant themes that emerged reflect the importance of comics in the context of elementary Education, including children, reading comprehension, and the use of comics as a learning medium. This study concludes that comics play a strategic role in increasing reading interest among elementary school students, as evidenced by a systematic mapping of research trends and dynamics over the past decade, conducted through bibliometric analysis. These findings have important implications for policy developers in the field of Education, including the support of inclusive and innovative literacy programs in primary education, the opening up of opportunities for cross-disciplinary collaboration, and providing a basis for longitudinal research on the long-term impact of comics on children's literacy development.